Gestión participativa de los recursos hídricos de la microcuenca Buenavista, en base a la zonificación ecológica y socioeconómica - Loaiza Carrión, Ermel Rodrigo (2014)
The watershed “Buenavista” where this research was developed is located in “Chaguarpamba” canton, its main wather shed is “ Buenavista creek. It constitutes part of the Puyango-Tumbes bi-national river basin and it is located among the flat coordinates: N: 9562200 m and 9570200 m; E: 640000 m and 646000 m. The topic of the research was to make the ecological and socio-economic zoning of “Buenavista” micro-watershed. It provides water to the town that has same name, based on the participative management of the hydric watershed resources with a view to contribute with a good management and sustainability of resources and good living of population. it was analyzed as a starting point the reality in order to establish what methodology was going to be used. To establish each objective it was used the analytic–synthetic method - analogical, deductive-inductive-deductive. The techniques used were documentaries and field investigation. It was collected information such as maps and aerial photographs of the area; It was used direct observations; field surveys; laboratory analysis; surveys; interviews and workshops; which allowed to obtain results as maps of distribution of the population in the micro basin, map of the road network, map of conflicts of land use, map of ecological zoning, map of the current model of the territory, water availability, average annual flow map; and map of the Micro-watershed management proposal. “Buenavista” Micro basin, has a surface area of 4.277,7 hectares and presents 10 territorial zones; However, as a strategy for its management, it is divided into five areas: 1. For conservation and protection of forests; 2 livestock and agricultural areas; 3. For reforestation ; 4 forest production.; and, 5. For civil development; considering as an alternative for its management "The model of participatory management for river basin", having as a possibility the purchase of lands in Chinchal and its surroundings where the flow that feeds “Buenavista” drinking water system is born , whereas considering the will of the majority of population wit a contribution of $ 4.00/family/ per month for the purchase of the above-mentioned lands with a view to ensure quality water, enough for different uses and in a permanent way, The existing surface flows are evident in the different water flows of the micro basin, they were measured during the development of this research, and the following main results were obtained: at the top part of Chinchal, water shed 1 and 2; 8 and 5 l/s, respectively; Guato Guato, 15 l/s; cold water 6 l/s; in the middle, part Chiquita creek with 65,66 l/s; or new Hacienda creek 107.8 l/s; Ombomba creeck 76.4 l/s; and, in the lower part, it is located Buenavista Creek that feeds the above-mentioned flows and other ones of minor importance, with an average total flow to be followed-up for three years of 405,6 l/s during the dry seasons, this value was obtained for personal inspections performed frequently in the critical months of August and September . It is important to mention, that this flow because of the depth of the creeck has a little interest and benefit for the population of the watershed; It is also necessary to mention, that water availability of first level obtained in the area of study reports the range of 38 to 620 mm/year of hydric map, the Buenavista Creek in its exit (junction with the Pan-American Highway) was 0.49 m3/sec per year. In relation to the proposal for the management of the micro basin it was proposed an integral participatory management model of the micro basin, considering among other things: to create a body of management of the micro basin that doesn't exist yet, to carry out afforestation with native species in selected areas with the participation of inhabitants, institutions and authorities of the micro basin. To promote the use of livestock areas. To diversify and to improve agricultural production systems. To ensure the sustainability of the natural and productive resources of the watershed; and to socialize the information. Finally, it is recommended to apply the model of participatory social management for watershed, the Buenavista watershed management. To train and raise awareness among the inhabitants children, youth and adults of Buenavista watershed, to persuade them about the importance that participatory social management of natural resources for sustainability purposes and improvement of the quantity has, quality and water opportunity for everyone so that it can enable to update and to enhance the production systems through the use of improved technology, according with this reality. To train the operator of the drinking water system to perform efficient technical management of it. To buy as soon as possible the lands of the upper part of the micro basin (Chinchal site and its surounded); and, to create the “WATER FUND”, through a monthly fee per each family.